Product management crash course and Trello fundamentals. (Packt Publishing, 2021)
A crash course to improve your product management skills and learn Trello essentials to build your career in product management About This Video Leverage on the templates, resources, vast expertise, and experience from a seasoned product manager Improve your skills with case studies and practical examples Ace your next product management interview In Detail Welcome to the Product Management and Trello Fundamentals Crash Course. This course is divided into two parts. In part 1, we will cover product management, and in part 2, we will cover Trello. In product management, we will unpack key product management concepts; we will see real-world examples of product management in action, and we will hear directly from successful product managers. But we will go beyond that into tools that product managers use in their role as well as the tips and tricks that characterize successful product managers. In the Trello Fundamentals part, we will walk through Trello essentials and basics such as how to set up Trello Boards and how to use cards, into more advanced functionality such as using addons, templates, and automation. This course has been designed from the ground up with a focus on simplicity and practicality, utilizing a wide range of educational techniques. By the end of this course, you will gain a good understanding of Trello and be ready to build your career in product management. Who this book is for For this course, no preparation is needed. Little or no previous work-related skill, knowledge, or experience is needed. This course is for beginners.